The Influence of Craftsmen's Experience on Construction Project Productivity in the Cirebon Region - Fauzan, Raihan; Rachman, Mochammad Harish Syafa'atur; Pratama, Herdi Adhi; Kusumastuti, Indah Hariati (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the influence of craftsmen's experience on construction project productivity in Cirebon. Using a productivity rating method based on perception, productivity was quantitatively measured through foreman observations. The results indicate that craftsmen's experience has a significant influence, contributing 40.4% to productivity. A strong positive correlation (ρ = 0.557) was also found between experience and work quality, indicating that more experienced workers tend to be more productive and efficient. The implications of this study emphasize that workers' experience is a key factor in achieving optimal productivity. Additionally, work quality, safety, and discipline are essential elements that must be considered to enhance project success.